Adaptability and stability of wheat cultivars at different sowing dates in the state of Paraná, Brazil - Silva, Raphael Rossi (2012)
The objective of this work was to identify the best sowing dates and to evaluate the adaptability and stability of wheat cultivars in two wheat growing regions of the state of Paraná, Brazil. Seven cultivars were evaluated at Guarapuava and nine at Palotina as to grain yield, at four sowing seasons, in 2006, 2007 and 2008. The experimental design was a randomized complete block design, with four and three replicates, for Guarapuava and Palotina, respectively. The methodologies REML/BLUP and genotype main effect and genotype x environment interaction (GGE biplot) were used for adaptability and stability analysis, and the AMMI model was used to identify the best sowing dates. Sowing in July, at Guarapuava, and in April, at Palotina, maximized grain yield. The cultivars Safira, at Guarapuava, and CD 113, at Palotina, are stable, highly adapted and show high grain yield.